ANALISIS FAKTOR-FAKTOR PENENTU KINERJA PROFITABILITAS BANK PERKREDITAN RAKYAT (BPR) KONVENSIONAL DI SUMATERA BARAT - Afriyeni, Afriyeni; Fernos, Jhon (Jurnal Benefita, 2018)
The existence of Rural Banks (BPR) in assisting the development and economic progress of the community, especially in rural areas is very important. The purpose of this article is to examine and analyze the factors that determine the performance of the profitability of conventional rural banks in West Sumatra. To test the effect of each variable CAR, LDR, BOPO, and NPL on profitability (ROA) statistical methods and data processing are used with the SPSS program. The type of data used is secondary data obtained from Bank Indonesia, namely the conventional BPR Publication Report in West Sumatra in 2012-2016. The population in this study is conventional BPR in West Sumatra and the sample is taken by purposive sampling method, so that 85 observations are obtained. Data were analyzed using multiple linear regression. Based on the results of the study found that the internal factors of the bank CAR, LDR, BOPO and NPL have a significant effect on the profitability (ROA) of conventional BPR in West Sumatra. Keberadaan Bank Perkreditan Rakyat (BPR) dalam membantu perkembangan dan kemajuan ekonomi masyarakat terutama di wilayah pedesaaan sangat penting. Tujuan dari artikel ini adalah untuk menguji dan menganalisis faktor-faktor yang menjadi penentu kinerja profitabilitas BPR konvensional di Sumatera Barat (Sumbar). Untuk menguji pengaruh dari masing-masing variabel CAR, LDR, BOPO, dan NPL terhadap profitabilitas (ROA) digunakan metode statistik dan pengolahan data dengan program SPSS. Jenis data yang digunakan adalah data sekunder yang diperoleh dari Bank Indonesia yakni Laporan Publikasi BPR konvensional di Sumbar tahun 2012 – 2016. Populasi dalam penelitian ini BPR konvensional di Sumatera Barat dan pengambilan sampel dengan purposive sampling method, sehingga diperoleh sebanyak 85 pengamatan. Data dianalisis dengan menggunakan regresi linear berganda. Berdasarkan hasil penelitian ditemukan bahwa faktor-faktor internal bank CAR, LDR, BOPO dan NPL berpengaruh signifikan terhadap profitabilitas (ROA) BPR konvensional di Sumatera Barat.